Nitrate Utilization by Nitrate Reductase-deficient Barley Mutants - Warner, Robert L. (1981)
Two nitrate reductase-deficient barley mutants were studied for growth on nitrate and ammonium sources of nitrogen and for resistance to chlorate. Although nitrate reductase-deficient mutants in some species are chlorate-resistant (unable to reduce chlorate to chlorite), the barley mutants used in these studies when grown on nitrate and treated with chlorate were only slightly more resistant to chlorate than the control. When grown to maturity on vermiculite supplemented with either nitrate or ammonium nutrient solutions, the mutants produced as much dry weight and reduced nitrogen per plant as the control. The in vivo and in vitro nitrate reductase activities in the roots and shoots of the mutants grown on nitrate were consistently less than 10% of the control. To avoid the possibility that the mutants received reduced nitrogen from microbial sources, excised embryos were cultured under sterile conditions. Again the mutants were capable of growth and reduced nitrogen accumulation with nitrate as the sole source of nitrogen. In spite of the low apparent nitrate reductase activity, the nitrate reductase-deficient mutants are capable of substantial nitrate reduction.